Pembelajaran Berbasis Teknologi Pada Materi Sejarah Kebudayaan Islam di MTs Negeri 3 Purbalingga - Khoirun Nisa Fahmi Utami, Khoirun Nisa; Harisatunisa (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research aims to describe how the technology-based learning process on Islamic Cultural History material at MTs Negeri 3 Purbalingga and the positive impact of technology-based learning on Islamic Cultural History material on student motivation at MTs Negeri 3 Purbalingga, particularly in class VIII B. Islamic Cultural History is often viewed as an uninteresting and somewhat theoretical subject because it contains material that requires a deep understanding of Islamic history and civilization, such as the biographies of Islamic scholars. This results in students becoming lazy and finding it difficult to grasp the lessons. With the presence of technology, it is hoped that it can foster students' interest in the subject of Islamic Cultural History. Descriptive research with a qualitative approach is used in this study, where observation, interviews, and documentation techniques are employed to collect research data. Meanwhile, data reduction, presentation, and conclusion drawing techniques are used to analyze the collected research data. The results of this study illustrate the technology-based learning process with planning stages. Then the implementation stage, which explains the technology-based learning activities starting from the introduction, core activities, to the conclusion of the learning. Next is the evaluation stage of learning that uses technology as a form of assessment. Technology-based learning in Islamic Cultural History can create a positive impact on students' learning motivation, one of which can change students' perceptions of Islamic Cultural History learning from initially feeling boring to being enjoyable and interactive.